2004
DOI: 10.1152/ajpcell.00394.2003
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of collecting duct aquaporin-2 by metabolic acidosis: role of vasopressin

Abstract: Amlal, Hassane, Sulaiman Sheriff, and Manoocher Soleimani. Upregulation of collecting duct aquaporin-2 by metabolic acidosis: role of vasopressin. Am J Physiol Cell Physiol 286: C1019-C1030, 2004. First published December 24, 2003 10.1152/ ajpcell.00394.2003.-Metabolic acidosis is associated with alteration in fluid and electrolyte reabsorption in a number of nephron segments. However, the effects of metabolic acidosis on urine osmolality and aquaporin-2 (AQP-2) remain poorly understood. In these studies, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 53 publications
(98 reference statements)
1
45
0
Order By: Relevance
“…Experiments using simultaneous mutations of S256 and S261 showed that the phosphorylation or dephosphorylation state of S261 does not alter the dominant effect driven by the phosphorylation and dephosphorylation state of S256 in VP-induced AQP2 trafficking. It remains possible that the effects that we have observed in our transfected cell model may not exactly mimic AQP2 trafficking in principal cells in vivo in this instance, although LLC-PK cells have proven to be a reliable predictor of the in vivo AQP2 signaling machinery in many previous studies (1,2,7,12,(21)(22)(23)(24)(25). Also, it is possible that more subtle kinetic differences in the intracellular trafficking pathway of AQP2 occur that were not detectable using the present techniques.…”
Section: Resultsmentioning
confidence: 79%
“…Experiments using simultaneous mutations of S256 and S261 showed that the phosphorylation or dephosphorylation state of S261 does not alter the dominant effect driven by the phosphorylation and dephosphorylation state of S256 in VP-induced AQP2 trafficking. It remains possible that the effects that we have observed in our transfected cell model may not exactly mimic AQP2 trafficking in principal cells in vivo in this instance, although LLC-PK cells have proven to be a reliable predictor of the in vivo AQP2 signaling machinery in many previous studies (1,2,7,12,(21)(22)(23)(24)(25). Also, it is possible that more subtle kinetic differences in the intracellular trafficking pathway of AQP2 occur that were not detectable using the present techniques.…”
Section: Resultsmentioning
confidence: 79%
“…However, the 0.28 M NH 4 Cl solution is hypertonic and will cause an increase in plasma osmolality and a subsequent stimulation of the plasma level of vasopressin. 12,13 The drinking method of the 0.28 M NH 4 Cl solution will also decrease the appetite and body weight of rats compared with that of control rats. Taken together, the drinking method of the 0.28 M NH 4 Cl solution induces metabolic acidosis with dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, it is not known whether metabolic acidosis affects AQP2 expression in the kidney. Recently, Amlal et al 12 reported that metabolic acidosis increased AQP2 expression in the collecting ducts by the activation of plasma vasopressin level. They used a 0.28 M NH 4 Cl solution for the induction of metabolic acidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies, including micropuncture experiments, suggested that systemic acid-base disturbances specifically influence Ca 2ϩ and Mg 2ϩ reabsorption in DCT/CNT (2,10). Hypothetically, regulation of Ca 2ϩ and Mg 2ϩ transport proteins in these nephron segments could be involved in the altered renal divalent excretion secondary to changes in acid-base status, as was shown for other renal transporters and channels (11)(12)(13)(14). We previously demonstrated that tacrolimus (FK506)-induced Ca 2ϩ and Mg 2ϩ wasting as well as thiazide-induced hypomag-nesemia are associated with decreased renal expression of Ca 2ϩ and/or Mg 2ϩ transporters (15,16).…”
mentioning
confidence: 91%